Stabilization heat treatment and functional response of 0.65[Pb(Mg1/3Nb2/3)O3]-0.35[PbTiO3] ceramics. (November 2017) - Augustine, Pius; Samanta, Shibnath; Rath, Martando; Miryala, Muralidhar; Sethupathi, K.; Murakami, Masato; Ramachandra Rao, M.S.
Graphical abstract: Highlights: Stabilization heat treatment in two different patterns. Removal of unused PbO and realization of stoichiometric ceramic. XRD, EDS, XPS, SEM, Hystersis and Dielectric studies. Enhanced dielectric and ferroelectric response. Structural and microstructural correlation to functional response. Abstract: We report on the heat treatment to stabilize 0.65[Pb(Mg1/3 Nb2/3 )O3 ]-0.35[PbTiO3 ] ceramics and its effect on the functional response. The stabilization heat treatment at 1050 °C for 4 h was effective in removing un-reacted PbO from the ceramics, which was confirmed through the measurements of dielectric and ferroelectric properties for a series of samples with different PbO contents. We also found that the stage of the stabilization heat treatment affected the sample properties. When this treatment was administrated to the sample during calcination, it exhibited excellent ferroelectric behavior. On the other hand, the same stabilization heat treatment given to the compacted pellet prior to sintering resulted in excellent dielectric properties with comparatively low ferroelectric hysteresis.